Electrically conductive, hydrophobic, UV protective and lightweight cotton spunlace nonwoven fabric coated with reduced graphene oxide - GÜLTEKİN, BEKİR CENKKUT (My University, 2022)
Abstract: In this study, cotton spunlace nonwoven fabrics with four different basis weights were coated with graphene oxide (GO) by conventional dip coating method which is one of the most simple and effortless process in textile industry. The graphene oxide coated cotton nonwoven fabrics were immersed in an aqueous sodium dithionite solution in order to obtain reduced graphene oxide (RGO) coated cotton spunlace nonwoven fabrics. The obtained nonwoven fabrics became electrically conductive with very low surface electrical resistivity of 5.98 × 102 W/sq for the 70 g/m2 basis weight nonwoven fabric. The color measurements and reflectance spectrophotometry were performed in order to identify the coating and reduction process of GO on cotton nonwoven fabrics. The hydrophobic characteristic of the GO and RGO coated cotton nonwoven fabrics were determined by the means of water contact angle. The ultraviolet (UV) blocking ability of the cotton nonwoven fabric both coated with GO and RGO were analyzed by the UV transmittance analyzer. The water contact angle results revealed that the hydrophilic cotton nonwoven fabric became hydrophobic due to the reduction of GO. It was also found that the ultraviolet protection factor (UPF) depends on the basis weight of the cotton nonwoven fabric and the reduction of GO. Key words: Cotton, nonwoven fabric, graphene oxide, coating, reduction
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Engineering, Computing & Technology (ENG); Cotton; nonwoven fabric; graphene oxide; coating; reduction; ELECTROMAGNETIC SHIELDING EFFECTIVENESS; ELECTRODE; REDUCTION; TEXTILES; VAT